Analisis Kombinasi Metode Pengukuran Terestrial Dan Fotogramteri Pada Penyusunan Master Plan Sekolah NU Kota Tarakan - Edy Utomo; Wahyu Hidayat; Yudi Chandra (Borneo Engineering : Jurnal Teknik Sipil, 2022)
Survey and mapping work can basically be done by various methods. Like terrestrial, photogrammetric and extraterrestrial methods, which generally have the same goal of projecting the earth surface into a topographic map at a certain scale. In this study, an exploration was carried out regarding the collaboration between the terrestrial method and photogrammetry in the depiction of topographic maps, which would provide more representative results. The object of this research is the land belonging to the PCNU of Tarakan City, which will be built as a school, where this land has a fairly steep surface relief. This study also provides comparison results from the application of the two measurement methods, which are applied to extreme land. Based on the analysis carried out, several research results were obtained, namely: The average percentage of the X,Y and Z coordinate of the two methods was 12,71% where a significant difference occurred in the altitude or Z component, which was 38,12% while the coordinate component X and Y have a difference value of 0,00%. The shape of the depiction of the soil relief produces an image that is close to the real condition, this can be seen from the contour shape that follows the shape of the soil relief on the sand cliff and tends to be random. The method that is suitable for use in the case of the object of this research is the photogrammetric method, because the steep terrain and irregular soil relief make it difficult to apply the terrestrial method, besides that the terrestrial method with the application of sampling point coordinates is not accurate to produce relief of the ground surface conditions actually.